Novel Xylene-linked Maltoside Amphiphiles (XMAs) for membrane protein stabilisation - Cho,KH; Du,Y; Scull,NJ; Hariharan,P; Gotfryd,K; Loland,CJ; Guan,L; Byrne,B; Kobilka,BK; Chae,PS (Chemistry - A European Journal, 2015)
Membrane proteins are key functional players in biological systems. These biomacromolecules contain both hydrophilic and hydrophobic regions and thus amphipathic molecules are necessary to extract membrane proteins from their native lipid environments and stabilise them in aqueous solutions. Conventional detergents are commonly used for membrane protein manipulation, but membrane proteins surrounded by these agents often undergo denaturation and aggregation. In this study, a novel class of maltoside-bearing amphiphiles, with a xylene linker in the central region, designated xylene-linked maltoside amphiphiles (XMAs) was developed. When these novel agents were evaluated with a number of membrane proteins, it was found that XMA-4 and XMA-5 have particularly favourable efficacy with respect to membrane protein stabilisation, indicating that these agents hold significant potential for membrane protein structural study.